Los medios de comunicación y el Arca de Noè: la sociología del futuro - Bouza, Fermín (SocietàMutamentoPolitica, 2015)
Construction of modernity brings a new individualism and a constant presence of the media. The new individuals are giving the construction of the public agenda to the media, who interpret the theory of ongoing economic crisis, which has forced us to rethink the economic and political order. The metaphor of Noah’s Ark is used to visualize a situation where we must seriously begin to choose what to keep of the current scrap. The sociology of the future, as the Ark, should evaluate this modern history and help build a possible plan for a livable future.